Improving chemotherapeutic drug penetration in tumors by vascular targeting and barrier alteration - Curnis, Flavio (American Society for Clinical Investigation, 2002)
Drug delivery and penetration into neoplastic cells distant from tumor vessels are critical for the effectiveness of solid-tumor chemotherapy. We have found that targeted delivery to tumor vessels of picogram doses of TNF-α (TNF), a cytokine able to alter endothelial barrier function and tumor interstitial pressure, enhances the penetration of doxorubicin in tumors in murine models. Vascular targeting was achieved by coupling TNF with CNGRC, a peptide that targets the tumor neovasculature. This treatment enhanced eight- to tenfold the therapeutic efficacy of doxorubicin, with no evidence of increased toxicity. Similarly, vascular targeting enhanced the efficacy of melphalan, a different chemotherapeutic drug. Synergy with chemotherapy was observed with 3–5 ng/kg of targeted TNF (intraperitoneally), about 10(6)-fold lower than the LD(50) and 10(5)-fold lower than the dose required for nontargeted TNF. In addition, we have also found that targeted delivery of low doses of TNF to tumor vessels does not induce the release of soluble TNF receptors into the circulation. The delivery of minute amounts of TNF to tumor vessels represents a new approach for avoiding negative feedback mechanisms and preserving its ability to alter drug-penetration barriers. Vascular targeting could be a novel strategy for increasing the therapeutic index of chemotherapeutic drugs.